EVALUATION OF THE USE OF ACCOUNTING AND FINANCIAL TOOLS IN A SMALL RURAL PROPERTY IN THE CITY OF IRANDUBA, AMAZONAS (REMUNOM, 2025)
Family farming on the Amazon continues to face a centuries-old challenge in adopting management and production methods and tools based on contemporary science and technology, such as accounting and financial tools for planning and monitoring the assets and financial resources of its enterprises. Therefore, this study aimed to evaluate the use of accounting and financial tools on a small rural property operating in the family farming segment located in the city of Iranduba, Amazonas state. The method used consisted of collecting data on the social, productive, and accounting-financial aspects of the enterprise, collected through interviews and on-site observation, organized and presented in summary tables. The social results showed low education levels and a family composed of only three people, considered young. The productive aspects presented a small variety of products, some of which were organic, with a small cultivation area and low production. The accounting-financial aspects demonstrated a lack of use of any planning and control tools. The conclusion shows that the lack of accounting and financial rationality contributes significantly to the continued poverty that is so common in Amazonian family farming.